Suomen kilpailukykyongelman luonne; The Nature of the Finnish Competitiveness Problem - Mika Maliranta; Vesa Vihriälä (The Research Institute of the Finnish Economy (ETLA), 2013)
– We assess Finland's competitiveness in the light of various, mainly short-term indicators. It turns out that the weak export market performance over the last few years is linked to the deterioration of profitability of production in Finland. A better export and employment performance requires a decline of relative unit labour costs and an improvement of business profitability. Wage moderation is necessary for this to happen. On the other hand, the determinants of Finland's long-term competitiveness are quite good and maintaining and developing them should remain a key element of economic policy also in the future.
Keywords: F40; E25; E64; J31; O47; 330; Competitiveness; Profitability; Productivity; Export performance; Employment; Internationaler Wettbewerb; Rentabilität; Erwerbstätigkeit; Lohnstückkosten; Finnland